2017
DOI: 10.2298/jsc160707017b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hematite nanorods on the mechanical properties of epoxy resin

Abstract: The mechanical properties of nanocomposites obtained by incorporation of fairly uniform hematite nanorods (α-Fe 2 O 3 NRs) into epoxy resin were studied as a function of the content of the inorganic phase. A thorough microstructural characterization of the α-Fe 2 O 3 NRs and the nanocomposites was performed using transmission electron microscopy (TEM) and atomic force microscopy (AFM). The TEM measurements revealed rod-like morphology of the nanofiller with a uniform size distribution (8.5 nm×170 nm, dia-meter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Bogdanovic et al . determined the effect of α‐Fe 2 O 3 on epoxy resin by DSC . Except for the sample with the highest content of α‐Fe 2 O 3 nanorods (NRs) (1.0 wt %), all the other composite samples had a lower T g than that of the pure epoxy resin, as shown in Figure .…”
Section: Effect Of Nanoparticles On the Thermal Stability Of Resin Mamentioning
confidence: 99%
“…Bogdanovic et al . determined the effect of α‐Fe 2 O 3 on epoxy resin by DSC . Except for the sample with the highest content of α‐Fe 2 O 3 nanorods (NRs) (1.0 wt %), all the other composite samples had a lower T g than that of the pure epoxy resin, as shown in Figure .…”
Section: Effect Of Nanoparticles On the Thermal Stability Of Resin Mamentioning
confidence: 99%
“…It can be observed that the weakest increase in tensile strength is observed for the samples LDPE/0.5%HR1 and LDPE/1%HR1 due to the use of rod-shaped hematite particles, which show the highest tendency to agglomerate when used in higher content because of their specific geometry and the ability to aggregate. It is known that there is a tendency for rod-like filler nanoparticles to form agglomerates in the surrounding media, which limits the use of such 1D nanofiller types for the reinforcement of polymers [30]. Bogdanović et al [30] showed that hematite nanofiller has an influence on the improvement of the mechanical properties of an epoxy polymer matrix when the composites are prepared with low filler content (up to 1 wt.%).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It is known that there is a tendency for rod-like filler nanoparticles to form agglomerates in the surrounding media, which limits the use of such 1D nanofiller types for the reinforcement of polymers [30]. Bogdanović et al [30] showed that hematite nanofiller has an influence on the improvement of the mechanical properties of an epoxy polymer matrix when the composites are prepared with low filler content (up to 1 wt.%). There is a possibility for the agglomeration of filler particles in the polymer matrix when the filler content exceeds a certain value, which influences the decrease in the mechanical properties [31].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interesting characteristics of epoxy include low shrinking after cure, good adhesion to different substrates, great stiffness, low creep, chemical and thermal resistance, low cost and high significance of hardness and strength. Epoxy resins exhibit some advantages in mechanical properties [9][10][11][12][13]. These excellent properties make epoxy resin a selection resin for many high-performing engineering applications [14].…”
Section: Introductionmentioning
confidence: 99%